Attitudes and perceptions of English as a foreign language students on blended learning and learner autonomy in a private university of China - Cao, Yongmei; Jeyaraj, Joanna Joseph; Razali, Abu Bakar (Society for Research and Knowledge Management, 2024)
Blended learning (BL) is becoming increasingly popular and a trend in higher education in the twenty-first century. The purpose of this study was to explore the attitudes and perceptions of English as a Foreign Language (EFL) learners toward the current implementation of BL and their learner autonomy (LA) development in a private university in China. It employed a qualitative case study, and the data was collected from five undergraduate students majoring in English through interviews, observations and reflective journals. Through thematic analysis of the data, the study concluded that EFL students at this university generally held negative attitudes toward the BL model and perceived the development of LA in this model as ineffective. Four themes related to the negative attitudes and perceptions emerged. First, a shortage of time was a common issue among students, and they felt mentally and physically overwhelmed by the blended tasks. Second, there was a lack of complementarity and integration between online and face-to-face instruction in the BL model. Third, students noted a lack of support and timely feedback from teachers in the online part of the BL model. Finally, more supervision was needed in terms of student characteristics. The findings have implications for future BL curriculum design and delivery, pedagogical adjustments and support for autonomous learning. More empirical studies focusing on the pedagogical design and the cultivation of EFL learners’ intrinsic motivation for autonomous English learning in the BL environment are essential to address the current situation. © 2024 Society for Research and Knowledge Management. All rights reserved.